Enhancement of mechanical and biological properties of calcium phosphate bone cement by incorporating bacterial cellulose. (10th November 2019) - Zhang, Quanchao; Lei, Zhili; Peng, Mengxia; Zhong, Meiling; Wan, Yizao; Luo, Honglin
ABSTRACT: Low mechanical strength of calcium phosphate cement (CPC) limits its clinical application as a bone replacement. Herein, for the first time, we selected bacterial cellulose (BC) fibres to reinforce CPC. The BC-reinforced CPC (BC/CPC) composites with varying BC content were prepared and compared in terms of microstructure, compressive strength and cellular responses. Scanning electron microscope (SEM) images revealed the uniform dispersion of BC in CPC matrix. Fourier-transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) results confirmed the interfacial coordination interaction between BC and CPC. It was found that the introduction of BC enhanced the compressive strength of CPC, and the optimal BC content was 2 wt.%. Moreover, cell studies showed that BC/CPC composites exhibited better cell performance than bare CPC. The results have demonstrated that a new CPC composite with enhanced mechanical performance and cellular responses may be developed by using BC as reinforcement.